Learning to live with irregular migration: towards a more ambitious debate on the politics of 'the problem'. Issue 1 (3rd April 2017) - McNevin, Anne
Abstract: What might be gained by learning to live with 'the problem' of irregular migration, rather than attempting to solve it? This article engages two senses of 'the problem' at stake: first, the ongoing nature of displacement and migration and second, the contested justice claims that sit behind different policy perspectives. The second sense of the problem (its political dimension) is rarely addressed explicitly in public debate. Yet direct engagement with the political dimension offers the potential to unlock debate from a polarised impasse. To make this argument, I first diagnose debate on irregular migration in terms of three archetypal positions and examine their implicit justice claims. I then argue for a more ambitious debate that pushes contending justice claims to their logical extensions. Debate of this kind requires a more coherent defence of justice claims, whether they are based in communitarian, cosmopolitan, anti-capitalist or hybrid values with respect to citizenship and political community. The article concludes with an illustration of how this approach can generate momentum for less circular, more sustainable and politically achievable policy responses. The argument is made with reference to illustrative examples from Australia and Europe but holds for a variety of contexts where 'the problem' is framed in similar ways.